The geographic diversity of nontuberculous mycobacteria isolated from pulmonary samples: A NTM-NET collaborative study. - Keane, Joseph (My University, 2013)
A significant knowledge gap exists concerning the geographical distribution of nontuberculous mycobacteria (NTM) isolation worldwide. To provide a snapshot of NTM species distribution, global partners in the NTM-Network European Trials Group (NET) framework (www.ntm-net.org), a branch of the Tuberculosis Network European Trials Group (TB-NET), provided identification results of the total number of patients in 2008 in whom NTM were isolated from pulmonary samples. From these data, we visualised the relative distribution of the different NTM found per continent and per country. We received species identification data for 20 182 patients, from 62 laboratories in 30 countries across six continents. 91 different NTM species were isolated. Mycobacterium avium complex (MAC) bacteria predominated in most countries, followed by M. gordonae and M. xenopi. Important differences in geographical distribution of MAC species as well as M. xenopi, M. kansasii and rapid-growing mycobacteria were observed. This snapshot demonstrates that the species distribution among NTM isolates from pulmonary specimens in the year 2008 differed by continent and differed by country within these continents. These differences in species distribution may partly determine the frequency and manifestations of pulmonary NTM disease in each geographical location.
PUBLISHED
Keywords: Nontuberculous mycobacteria (NTM); Mycobacterium avium complex (MAC) bacteria; Geographical distribution; Immunology, Inflammation & Infection